PENERAPAN TEKNOLOGI DRY ROOM INFRARED DAN INOVASI CANTING CAP UNTUK MENGEMBANGKAN BISNIS BATIK DAN SONGKOK BATIK DI DESA REK KERREK PAMEKASAN - Nur Sayidah; Siti Marwiyah; Liosten Rianna Roosida Ully Tampubolon; Muharrom Muharrom; Septian Dwi Putranto; Puput Maya Sari; Nurul Leny Setiana; Zulfatun Naimah (Universitas Mataram, 2025)
The drying of batik songkok raw materials in Rek Kerrek Village, Pamekasan Regency, is done by relying on sunlight. The time required is 3 days. When the weather is cloudy and rainy, the drying time is longer, namely 1 week and the batik color is dull. The batik process is still conventional with canting which is hand-drawn and motifs that rely on ancestral heritage. The process of batik with manual canting takes 2-3 days to 1 month per sheet. The problems faced are the long time for processing and drying batik so that production capacity, expensive batik prices and the competitiveness of batik products are still low. The objective of the PDB program is to provide technological innovations in the form of an infrared dry room drying machine to speed up the drying time of batik and an innovation in canting caps to speed up the batik processing time. This innovation increases production capacity, sales volume, and the competitiveness of batik products. The methods used are training, mentoring and practice of technological innovations for partners. The results of the program are: 1) the infrared dry room drying machine (partner-1) and the innovation in canting caps (partner-2) increase production capacity and quality, sales volume and the competitiveness of batik products. The infrared dry room dryer speeds up drying time to approximately 90 minutes. The batik process using a canting cap simplifies the process and reduces the completion time to 3 hours.